From the Infography to the Display of Data: Impact of Big Data in the design of information - Salvat, Guiomar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2018)
We present a work on the processes that take place around the visualization of the information. From the graphic visualization techniques used since prehistory, the concept of infographics emerged in the journalistic field with the digitalization of processes in the 90s. The incorporation of Big Data gives new functions to the data visualization and then forces us to rethink whether both terms refer to the same practices of graphic representation, or are independent technical processes with their own entity, and in that case, determine what corresponds to each one.